Lymphoid architecture - the meeting places that spark the body’s immune reactivity: design and dynamics 2 - Hunt, Simon (Henry Stewart Talks, 2021)
Formation of germinal centers within lymph nodes, T cells activation and function, B cell development and affinity maturation, Comparison of how secondary and tertiary lymphoid organs developed, Immunology of malignant tumours